Historical Perspective: Using the Past to Study the Present - Lawrence, Barbara (Academy of Management Review, 1984)
Historical perspective refers to understanding a subject in light of its earliest phases and subsequent evolution. This perspective differs from history because its object is to sharpen one's vision of the present, not the past. When historical perspective is overlooked in social research, researchers may draw misleading conclusions. Historical perspective expands research horizons by encouraging study of the relative stability of phenomena, providing alternative explanations for phenomena, and aiding problem formulation and research design.